2016
DOI: 10.1039/c6ra15520k
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic fracturing in methane-hydrate-bearing sand

Abstract: Hydraulic fracturing in methane-hydrate-bearing sand can generate laminar fractures and increase the effective permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 37 publications
6
66
0
Order By: Relevance
“…[35][36][37] At present, hydraulic fracturing, hydraulic cutting and hydraulic punching are commonly used as the primary methods to improve the permeability of coal for methane extraction and gas-disaster management. [38][39][40][41][42][43] But the coal seams would be wetted at the same time, which can bring some negative effect, such as occupying the seepage channel, increasing the ow resistance and impacting the gas desorption. [44][45][46] Moisture always coexists with gas in coal at all ve stages of gas recovery, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] At present, hydraulic fracturing, hydraulic cutting and hydraulic punching are commonly used as the primary methods to improve the permeability of coal for methane extraction and gas-disaster management. [38][39][40][41][42][43] But the coal seams would be wetted at the same time, which can bring some negative effect, such as occupying the seepage channel, increasing the ow resistance and impacting the gas desorption. [44][45][46] Moisture always coexists with gas in coal at all ve stages of gas recovery, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…According to Fan et al, the fracture length and width in weakly consolidated sandstone can be up to 28 m and 30 mm when using high‐efficiency fracturing fluid, respectively. In addition, Konno et al have also investigated the fracture characteristics in unconsolidated sediments by cyclic fracturing using X‐ray computed tomography. The researchers observed that the maximum fracture width can approach 60 mm after the second injection.…”
Section: Simulation Modelmentioning
confidence: 99%
“…Consequently, many investigations (eg, Refs. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] have been performed recently, and numerical simulations have still focused on depressurization that is aimed at commercial production from potential target areas. In practice, depressurization has also been widely adopted in field trials in Mallik, 34 the eastern Nankai Trough, 35,36 and the South China Sea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Konno et. al [15] investigated HF as a well stimulation method during gas recovery from gas hydrate reservoirs. They injected distillate water into methane-hydrate-bearing sand, which was in a three-dimensional confining stress state.…”
Section: Introductionmentioning
confidence: 99%